2019
DOI: 10.1016/j.fsi.2019.04.161
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to antibiotics affects saponin immersion induced immune stimulation and shift in microbial composition in zebrafish larvae

Abstract: In the last decades, pollution of the environment by large scale use of antibiotics in agriculture and human medicine have led to increased antimicrobial resistance in both the environment and the host animal microbiome. Disturbances in the host microbiome can result in impaired immunity and reduced resilience of aquaculture species. Here, we investigated whether environmentally measured levels of the commonly used antibiotics ciprofloxacin and oxytetracycline influences the host microbiome and susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…For example, a loss of gut diversity was observed in Atlantic salmon following oxytetracycline treatment [62], in channel catfish (Ictalurus punctatus) following florfenicol treatment [63], in fathead minnow (Pimephales promelas) after triclosan use [64] and in zebrafish following olaquindox treatment [65]. In contrast, in some cases, it has been reported that antibiotic treatment may even increase or cause a shift in species diversity, as shown for Atlantic salmon and zebrafish [12,13], and pacu (Piaractus mesopotamicus) [8] respectively. This is pertinent given that changes in diversity and evenness within the gut has been suggested to influence functional capacity and disease resilience [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a loss of gut diversity was observed in Atlantic salmon following oxytetracycline treatment [62], in channel catfish (Ictalurus punctatus) following florfenicol treatment [63], in fathead minnow (Pimephales promelas) after triclosan use [64] and in zebrafish following olaquindox treatment [65]. In contrast, in some cases, it has been reported that antibiotic treatment may even increase or cause a shift in species diversity, as shown for Atlantic salmon and zebrafish [12,13], and pacu (Piaractus mesopotamicus) [8] respectively. This is pertinent given that changes in diversity and evenness within the gut has been suggested to influence functional capacity and disease resilience [66].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the antibiotics used in the aquaculture industry are considered to be broad-spectrum, and may indiscriminately act on both the pathogenic and commensal constituents [11]. Perturbation of the gut microbiota following antibiotic exposure has been reported in various fish species [8,12,13] and may be associated with changes in microbial enzymatic activity, gene expression, and protein and metabolite synthesis [14]. In humans and other animals, antibiotic use may have prolonged effects on the gut bacterial composition, leading to widespread perturbations and the extinction of some species [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a loss of gut diversity was observed in Atlantic salmon following oxytetracycline treatment [62], in channel cat sh (Ictalurus punctatus) following orfenicol treatment [63], in fathead minnow (Pimephales promelas) after triclosan use [64] and in zebra sh following olaquindox treatment [65]. In contrast, in some cases, it has been reported that antibiotic treatment may even increase or cause a shift in species diversity, as shown for Atlantic salmon and zebra sh [12,13], and pacu (Piaractus mesopotamicus) [8] respectively. This is pertinent given that changes in diversity and evenness within the gut has been suggested to in uence functional capacity and disease resilience [66].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the antibiotics used in the aquaculture industry are considered to be broad-spectrum, and may indiscriminately act on both the pathogenic and commensal constituents [11]. Perturbation of the gut microbiota following antibiotic exposure has been reported in various sh species [8,12,13] and may be associated with changes in microbial enzymatic activity, gene expression, and protein and metabolite synthesis [14]. In humans and other animals, antibiotic use may have prolonged effects on the gut bacterial composition, leading to widespread perturbations and the extinction of some species [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the antibiotics used in the aquaculture industry are considered to be broad-spectrum, and may indiscriminately act on both the pathogenic and commensal constituents. Perturbation (dysbiosis) of the gut microbiota following antibiotic exposure has been reported in various fish species [8,11,12] and may be associated with changes in microbial enzymatic activity, gene expression, and protein and metabolite synthesis [13]. In humans and other animals, antibiotic use may have prolonged effects on the gut bacterial composition, leading to widespread dysbiosis and the extinction of some species [14].…”
Section: Introductionmentioning
confidence: 99%